The monetary dynamics of hyperinflation reconsidered - Luca Benati (University of Bern, Department of Economics, 2023)
Data from 20 hyperinflations provide no evidence of a Laffer curve for seignorage: rather, the relationship between money growth and seignorage has been uniformly positive at all inflation rates. Consistent with this, evidence shows that the most plausible money demand specification for hyperinflations is not Cagan's 'semi-log', which imposes a Laffer curve upon the data, but rather either the 'log-log', or a functional form close to it such as Benati, Lucas, Nicolini, and Weber's (2021), which produce a monotonically increasing relationship between money growth and seignorage. Compared to the semi-log, functional forms close to the log-log imply different properties for theoretical models of hyperinflations along two dimensions: (i) the equilibria's stability properties are reversed, with the high-inflation equilibrium being unstable under rational expectations; and (ii) there is the possibility of explosive inflation even in the presence of well-defined steady-states. I discuss the implications of this for the interpretation of specific historical episodes. Under the Weimar Republic, a plausible interpretation of the macroeconomic consequences of the invasion of the Ruhr is that it pushed the economy beyond the unstable steady-state, into the region of explosive inflation.
Keywords: 330